Synergistic effect of periodontitis and C-reactive protein levels on mortality: NHANES 2001-2004. - Miyeun Han; Whanhee Lee; Seoyeong Ahn; Moon Ho Kang; Hyeon Seok Hwang; Soie Kwon; Yaerim Kim; Jeonghwan Lee; Dong Ki Kim; Chun Soo Lim; Yon Su Kim; Jung Pyo Lee (PLoS ONE)
Periodontitis is associated with elevated C-reactive protein (CRP) levels. Although the coexistence of periodontitis and elevated CRP levels may heighten the risk of mortality, previous studies have not confirmed their synergistic effect. Understanding this interaction is crucial for identifying potential interventions to reduce mortality risk in individuals with periodontitis. This study aimed to assess the synergistic effects of periodontitis and elevated CRP levels on mortality in 7,938 adult individuals who participated in the National Health and Nutrition Examination Study 2001-2004. The association of periodontitis status and CRP levels with mortality was assessed using a survey-weighted Cox model. The interactive effect was estimated; the synergistic effect of CRP levels and periodontitis status on mortality was assessed using the relative excess risk due to interaction (RERI). Periodontitis was diagnosed in 1,065 (13.4%) participants. Compared with the participants without periodontitis and possessing CRP levels of ≤ 0.5 mg/dL, those with periodontitis (hazard ratio [HR], 1.38) or CRP levels of > 0.5 mg/dL (HR 1.23) had higher HRs. The participants with both periodontitis and CRP levels of > 0.5 mg/dL had the highest HR of 2.01. The additive scale interactive effect of the periodontal status and CRP levels, measured using RERI 0.41 (-0.07, 0.95), was positive and nearly significant in the total population. The synergy between the periodontal status and CRP levels was more prominent in the participants aged ≥60 years than that in younger individuals. Periodontitis with high CRP levels may indicate a high mortality rate, indicating the importance of active monitoring and intensive management of periodontitis and inflammatory markers.